The Effect Of Video Based Simulation Training On Neonatal Examination Competency Among Turkish Nursing Students - Gul Pinar; Ayse Akalin; Halime Abay (European Scientific Journal, ESJ, 2016)
Purpose: The aim of this study was to determine the effect of video based simulation training on nursing student’s competency of neonatal examination (NE) skill. Method: An experimental, randomized controlled design was used. This study conducted with 46 junior nursing students in Ankara, Turkey. Results: Average of the achievement test of experimental group after the video based simulation training was 13.48±1.44 and the mean score of OSCE was 18.43±2.46. The mean score of control group achievement test was 12.00±1.22 and the mean score of OSCE was 10.09±3.17. The results showed that simulation had a statistically significant effect on knowledge and skill of NE (p<0.05). Conclusion: The results indicated that video based simulation training improved NE competency in nursing students.